PENGARUH PEMBERIAN KOMPRES HANGAT DAN AROMATERAPI JASMINE TERHADAP PENGURANGAN NYERI MENSTRUASI (DISMINOREA) PADA REMAJA PUTRI DI DESA GUNUNG TERANG KECAMATAN KALIANDA: PENGARUH PEMBERIAN KOMPRES HANGAT DAN AROMATERAPI JASMINE TERHADAP PENGURANGAN NYERI MENSTRUASI (DISMINOREA) PADA REMAJA PUTRI DI DESA GUNUNG TERANG KECAMATAN KALIANDA - Refti, Weni Guslia; Agustina, Indar Fitri (WELL BEING, 2025)
Background: : Dysmenorrhea or painful menstruation is one of the most common gynecological problems experienced by women of all ages. The effects of improper handling will interfere with daily activities. So there are several treatments that can be done to reduce dysmenorrhoea, namely pharmacologically and non-pharmacologically with warm compress therapy and aromatherapy. Aims: To determine the effect of warm compresses and jasmine aromatherapy on reducing menstrual pain (dysmenorrhoea) in young women at  in gunung terang village, kalianda districtMethods: This study used a quasi-experimental design with a probability sampling technique using proportionate stratified random sampling of 40 students with a non-equivalent pretest-posttest with control group design. Result : The difference in the effectiveness test for reducing dysmenorrhea in the warm compress group obtained a p-value of 0.001 <0.05 and the effectiveness test for reducing dysmenorrhea in the jasmine aromatherapy group was 0.005 <0.05. The results of the effect test used an unpaired T-test, so H0 is reject and Ha is accepted, meaning that there is an influence between giving warm compresses and jasmine aromatherapy on decreased (dysminorrhoea) in young women at in gunung terang village, kalianda district. Conclusion: Jasmine aromatherapy is more effective in reducing dysmenorrhea pain than warm compresses.